Metabolically Healthy Overweight and Obesity Is Associated with a Healthy Lifestyle Pattern in Lebanese Adults Hwalla N, Naja F, Itani L, Nasrallah M, Tamim H, Nasreddine L (P04-177-19) - Hwalla, Nahla (Curr Dev Nutr, 2019)
OBJECTIVES: The study aims to identify lifestyle patterns in a sample of Lebanese adults and examine the association of these patterns with Metabolically Healthy Overweight and Obesity (MHOv/O). METHODS: This study is based on a cross-sectional survey of Lebanese adults living in Greater Beirut area (n = 305), and which was conducted in 2014. Dietary intake assessment was performed using an 80-item semi-quantitative food frequency questionnaire. The identification of MHOv/O was based on the ATP-III criteria. Principal Component Factor Analysis was implemented to derive lifestyle patterns, including variables related to dietary intake, eating at home, alcohol consumption, drinking water, sleeping difficulties, smoking and physical activity. RESULTS: Two lifestyle patterns were identified in the study population: the “Unhealthy” pattern which was characterized by cigarette smoking, fast food, soft drinks and alcohol consumption . Eating at home loaded negatively on this pattern. The “Healthy” lifestyle pattern was characterized by positive loadings of food groups such as milk and dairy products, fruits and vegetables. Sleeping difficulties loaded negatively on this pattern, while physical activity had a positive loading. Multiple logistic regression analyses was performed. The results showed that subjects belonging to the 4th quartile of the “Healthy” pattern scores had higher odds of MHOv/O as compared to those in the 1st quartile (OR: 4.04, CI:1.26–13.01). CONCLUSIONS: The findings of this study provided evidence on the combined effect of lifestyle factors in relation to cardiometabolic abnormalities that are complex and multifactorial in nature. The results highlighted the importance of focusing on ‘holistic’ lifestyle patterns modifications in designing and implementing culturally sensitive interventions in overweight and obese subjects. FUNDING SOURCES: Lebanese National Council for Scientific Research; University Research Board at the American University of Beirut); Medical Practice Plan at the American University of Beirut.